An Applied Study on Integration Edges of Failure and TOPSIS to Educational Environment Safety Assessment: A Case Study - Mojtaba Rezaie; Naser Shamskia; Hesam Varaee; Mahdi Rafieizonooz; Jang-Ho Jay Kim (Journal of Soft Computing in Civil Engineering, 2022)
A reliability and safety assessment for a bunch of listed schools can be challengeable for experts by the checklist system for safety reports. This paper aimed to respond to this challenge by merging the edges of failure 'EoF' and the technique for order of preference by similarity to ideal solution 'TOPSIS' to achieve an integrative approach for educational environment safety assessment. The qualitative assessment was implemented to detect safety faults in the case study area based on the results of the inspections. Then, the quantitative assessment was done to calculate critical points in edges of failure using the TOPSIS method. These points have been calculated for a bunch of listed schools that detected safety faults, and it also takes the form of the 'Jeopardous Pentagon' to calculate 'EoF Integration Mode'. It is an overall safety assessment to indicate performances region by region. This paper collected items of information about the twelve schools in Shahriar divided into three districts. Afterwards, a dangerous area is estimated to rank the existing options by the amount of achievement information. The first rank of the dangerous area between existence options is Shahriar two district. The most critical sides of the JP for first ranked reflect the human error 'RHE' and cultural governance 'CG' by values 0.989 and 0.989 for both intersection points. The combination of EoF and TOPSIS is recommended to apply for a physical and non-physical environment based on the safety checklist system.